Artificial Intelligence Influences Intelligent Automation in Tourism: A Mediating Role of Internet of Things and Environmental, Social, and Governance Investment - Tong, Lei; Yan, Wei; Manta, Otilia (Frontiers in Environmental Science, 2022)
Intelligent automation in travel and tourism is likely to grow in the future, which is possible due to advances in artificial intelligence (AI) and associated technologies. Intelligent automation in tourism is a socio-economic activity, which needs an explanation of theory and practice. The study objective is to know the predictive relationship between artificial intelligence and intelligent automation in tourism with mediating role of the internet of things (IoT), sustainability, facilitating adoption, and ESG investment. Designing valuable AI, promoting adoption, analyzing the implications of intelligent automation, and establishing a sustainable future with artificial intelligence are the fundamental constructs of this study. Research in these areas enables a systematic knowledge creation that shows a concentrated effort on the part of the scientific community to ensure the positive uses of intelligent automation in the tourist industry. A quantitative research approach was used to collect and analyze data. A purposive sampling technique was applied, and data was collected from four hundred two (N= 402) respondents. The results revealed that artificial intelligence has a predictive relationship with intelligent automated tourism. Similarly, IoT, sustainability, facilitating adoption, and ESG has influenced tourism. As conclusion, artificial intelligence design can improve tourism department if the intelligent automated framework was applied to it.